Enhanced dispersal capacity in edge population individuals of a rapidly expanding butterfly - Anaïs Dederichs; Klaus Fischer; Peter Michalik; Michaël Beaulieu (Ecology and Evolution, 2024)
Abstract Natural range shifts offer the opportunity to study the phenotypic and genetic changes contributing to colonization success. The recent range shift of the Southern small white butterfly (Pieris mannii) from the South to the North of Europe offers a prime example to examine a potential dispersal syndrome in range‐expanding individuals. We compared butterflies from the core and edge populations using a multimodal approach addressing behavioral, physiological, and morphological traits related to dispersal capacity. Relative to individuals from the core range (France), individuals from the edge (Germany) showed a higher capacity and motivation to fly, and a higher flight metabolic rate. They were also smaller, which may enhance their flight maneuverability and help them cope with limited resource availability, thereby increasing their settlement success in novel environments. Altogether, the behavioral, physiological, and morphological differences observed between core and edge populations in P. mannii suggest the existence of a dispersal syndrome in range‐expanding individuals. Whether these differences result from genetic and/or phenotypic responses remains, however, to be determined.